Hubungan Pemanfaatan Buku Kia Dengan Tingkat Pengetahuan Dan Tingkat Kecemasan Ibu Hamil Di Rsud Banyumas - Wardiyati; Isnaeni Rofiqoch (2023)
Pregnant women's knowledge about the use of MCH books is still lacking and is an obstacle in the formation of health behaviors of pregnant women, especially in terms of low interest in reading MCH books , supported by the high anxiety of pregnant women. Do not understand health information and have not implemented the health information contained in the MCH book properly. Research Objectives to determine the relationship between the use of MCH books with the level of knowledge and anxiety level of pregnant women at Banyumas Regional Hospital. Research Design Time cross sectional approach. The study sample of primigravida first trimester and second trimester primigravida. Sample 88 respondents. Analysis with Kendal's Tau test. The results showed That there was a relationship between the use of MCH books and the level of knowledge with the results of a P-Value value of 0.000 less than 0.05, which means that the higher the utilization of MCH books, the higher the level of knowledge. The relationship between the use of MCH books and the level of anxiety with the Kendal's Tau test obtained the results of a P-Value value of 0.101 greater than 0.05, meaning that both the use of MCH books anxiety tends to be high influenced by the low interest in reading MCH books and not understanding the contents of MCH books. It is hoped that midwives can increase the use of MCH books with the motivation of pregnant women to increase interest in reading and there is a follow-up understanding of MCH books every ANC.